2016
DOI: 10.1021/acs.joc.6b01258
|View full text |Cite
|
Sign up to set email alerts
|

Azine-Hydrazone Tautomerism of Guanylhydrazones: Evidence for the Preference Toward the Azine Tautomer

Abstract: Guanylhydrazones have been known for a long time and have wide applications in organic synthesis, medicinal chemistry, and material science; however, little attention has been paid toward their electronic and structural properties. Quantum chemical analysis on several therapeutically important guanylhydrazones indicated that all of them prefer the azine tautomeric state (by about 3-12 kcal/mol). A set of simple and conjugated azines were designed using quantum chemical methods, whose tautomeric preference towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…35 The characterization of the product by 1 H NMR spectroscopy in DMSO-d 6 confirms the formation of guanabenz in its preferred azine tautomeric state as it is evidenced from the presence of two broad singlets of two protons each at 5.81 and 5.84 ppm, which are the characteristic probe for the presence of the azine tautomer. 19 Further, the confirmation for the presence of azine tautomer was provided by 13 C NMR spectroscopy where a signal at δ 161.98 ppm was observed which is attributed to the C(NH 2 ) 2 carbon, a characteristic probe of the azine tautomer. From the 1 H NMR study, we observed the presence of only one isomer, and it is assumed to belong to the E-isomer of guanabenz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The characterization of the product by 1 H NMR spectroscopy in DMSO-d 6 confirms the formation of guanabenz in its preferred azine tautomeric state as it is evidenced from the presence of two broad singlets of two protons each at 5.81 and 5.84 ppm, which are the characteristic probe for the presence of the azine tautomer. 19 Further, the confirmation for the presence of azine tautomer was provided by 13 C NMR spectroscopy where a signal at δ 161.98 ppm was observed which is attributed to the C(NH 2 ) 2 carbon, a characteristic probe of the azine tautomer. From the 1 H NMR study, we observed the presence of only one isomer, and it is assumed to belong to the E-isomer of guanabenz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reaction mass was stirred to get clear solution, and The reaction mass was stirred at room temperature which resulted in the formation of precipitate of product in 1 h (Scheme 1). 19 The resultant precipitates were filtered and washed with water (2 × 2 mL) to remove the excess of NaOH. The precipitates were dried under reduced pressure to afford guanabenz free base in 96% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phenyl and thiophene rings are bio-isosters 26 , and the former offers more synthetic versatility, i.e., can be substituted for structure activity relationship (SAR) acquisition. We substituted isothioureas with guanylhydrazones, as the latter groups show good stability and a pKa range closer to neutrality due to the delocalization of their charge on three N atoms (favored azine form vs. disfavored hydrazone form, 4.5 ≤ ΔGT ≤ 6.5 Kcal/mol 27 , Supplementary Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…All reagents and solvents were purchased from the Sigma and Merck companies and were all used without further purification. All the 2‐benzylidenehydrazinecarboximidamide derivatives ( 3a ‐ n ) were prepared according to the known literature procedure 26 . Melting points were measured on a standard (Thermo) apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray crystallographic and theoretical studies of substituted guanyl hydrazones studies indicate that guanyl hydrazones should be represented as azines. The azine tautomers are found to be about 3 to 12 kcal/mol more stable than the hydrazone tautomers 26,27 …”
Section: Introductionmentioning
confidence: 94%